Campaign participation, spreading electronic word of mouth, purchase: How to optimise corporate social responsibility, CSR, effectiveness via social media? - Svetlana Bialkova; Stephanie te Paske (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The purpose of this paper is to investigate how to optimise corporate social responsibility (CSR) when communicating via social media. In particular, the communication type, cause proximity and CSR motives are addressed facing the increased demand for transparency and the grown consumers' expectations towards socially responsible brands. Design/methodology/approach - Online survey was developed, based on a profound literature review and a field research we did on the actual social media behaviour of socially responsible brands. Consumers attitudes and behavioural reactions in terms of willingness to participate in a campaign, to spread e-WOM and to purchase were investigated, as a function of CSR motives (value vs performance vs value and performance) and cause proximity (national vs international), respectively, with monologue (study 1) and dialogue communication type (study 2). Findings - Cause proximity enhanced the campaign participation, and this effect was pronounced for both, monologue and dialogue type of communication. CSR motives modulated the willingness to spread electronic word-of-mouth, and this holds for both, monologue and dialogue communication. Attitudes and purchase intention were highest when value- and performance-driven motives were communicated, but these effects appeared only when the message was in a dialogue form of communication. Message credibility and CSR motives credibility perception further modulated consumers response. Practical implications - The outcomes could be used in developing marketing (communication) strategies leading to values and revenues optimisation. Originality/value - The results are discussed in a framework of how CSR resonates via social media.
Keywords: 650; Attitudes; Cause proximity; Corporate social responsibility; Credibility; E-WOM; Purchase intention